2004
DOI: 10.1002/art.11488
|View full text |Cite
|
Sign up to set email alerts
|

Oligodeoxynucleotides containing CpG motifs can induce T cell–dependent arthritis in rats

Abstract: Objective. To investigate whether CpG oligodeoxynucleotides (ODNs) can induce or accelerate arthritis in rats.Methods. The CpG-induced response was studied by recording joint inflammation, cell activation in draining lymph nodes, and levels of the acute-phase reactant Conclusion. We demonstrated that injection with immunostimulatory CpG, both in phosphorothioatemodified and native forms, can induce a T celldependent joint-specific inflammation in LEW and LEW.1AV1 rat strains. This arthritis is preceded by sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…In this arthritis model, TLR4-deficient mice register delayed disease progression and decreased production of the proinflammatory mediators TNF-␣ and cyclooxygenase-2 in the synovial tissue, compared with wild-type animals. Immune responses provoked by bacterial DNA and CpG have been implicated in the onset of a Th1 cell-dependent and IL-1/IFN-␥-mediated joint-specific inflammation in LEW and LEW.1AV1 rat strains (47). In addition, numerous studies have shown expression of TLR4 and TLR2 in RA synovium (46,48).…”
Section: Discussionmentioning
confidence: 99%
“…In this arthritis model, TLR4-deficient mice register delayed disease progression and decreased production of the proinflammatory mediators TNF-␣ and cyclooxygenase-2 in the synovial tissue, compared with wild-type animals. Immune responses provoked by bacterial DNA and CpG have been implicated in the onset of a Th1 cell-dependent and IL-1/IFN-␥-mediated joint-specific inflammation in LEW and LEW.1AV1 rat strains (47). In addition, numerous studies have shown expression of TLR4 and TLR2 in RA synovium (46,48).…”
Section: Discussionmentioning
confidence: 99%
“…Yet pathogen derived molecules are capable of inducing experimental arthritis. For example, stimulation of TLR2, 3, 4, 9 can initiate and/or and aggravate numerous models of arthritis, for example those driven by streptococcal cell wall [32], dsRNA, LPS [33,34] and CpG DNA [35]. These studies clearly define roles for specific TLRs.…”
Section: Activation Of Dcs As Autoimmune Mediatorsmentioning
confidence: 97%
“…Under some conditions, these effects can result in inflammatory responses. Aggravating joint inflammation, which is characterized by cell activation, draining lymph nodes, and increased levels of the acute-phase reactant α1-acid glycoprotein in sera, has been discovered in CpG ODN-injected rats [58]. Svelander et al [58] demonstrated that injection with either a phosphorothioated or a native form of CpG ODN can elevate a T cell-dependent, joint-specific inflammation.…”
Section: Possible Side-effects Of Cpg Odnsmentioning
confidence: 97%
“…Aggravating joint inflammation, which is characterized by cell activation, draining lymph nodes, and increased levels of the acute-phase reactant α1-acid glycoprotein in sera, has been discovered in CpG ODN-injected rats [58]. Svelander et al [58] demonstrated that injection with either a phosphorothioated or a native form of CpG ODN can elevate a T cell-dependent, joint-specific inflammation. Their results indicated that exposure to bacterial DNA during infection might contribute to arthritis induction, due to TCCATGACGTTCCTGATGCT Edwardsiella tarda ↑ Survival rate [46] a The normal letter means CpG ODNs with phosphorothioate-linked backbone whereas the capitalized letter means CpG ONDs with phosphodiester-linked backbone.…”
Section: Possible Side-effects Of Cpg Odnsmentioning
confidence: 97%